PERTUMBUHAN TANAMAN GAHARU (Aquilaria spp) DENGAN PEMBERIAN MULSA DAN JENIS NAUNGAN PADA TANAH ULTISOL - Atikah, .; Muin, Abdurrani; Fahrizal, M (JURNAL HUTAN LESTARI, 2016)
Agarwood grows well if they are planted using appropriate technique. The research work aimed at finding information on the growth of Agarwood (Aquilaria spp) by giving mulching and shades on ultisol soil. This research work employed split plot design using a randomized block design consisting of types of shade (N) as main plot, mulching (M) as additional plot and the treatment was done for three times. The parameter being observed was height, diameter, number of leaves, and life expectancy of Agarwood. Shade factor consisted of three types; namely open shade (N1), paranet 60% (N2) and natural shade (N3). Mulching consisted of two types; without mulching (M0) and mulching (M1). The research findings showed that mulching (M1) had a significant effect on height, diameter, and leaves of Agarwood (Aquilaria spp). In addition, paranet 60% (N2) gave a very significant effect on life expectancy and had significant effect on diameter and leaves of Agarwood. Natural shade (N3) treatment impacted significantly on life expectancy of Agarwood while open shade treatment also had a significant impact on leaves of Agarwood. Paranet 60% and mulching (N2M1) treatment suggested a good growth on Agarwood. Keywords: Agarwood, growth, mulching, shade, and ultisol